TRANSLATION SHIFTS AND ACCEPTABILITY ON HONOR OF KINGS EVENT PAGE TEXTS - Nisa Choiru Ummah; Supriatnoko; Dewi Kurniawati (Politeknik Negeri Jakarta, 2025)
This study employs a qualitative descriptive method to describe the shift in sentence structure that occurs on the in-game event page of Honor of Kings, along with an assessment of translation quality (acceptability). The data collection techniques used were content analysis and Focus Group Discussion (FGD). In this study, 80 data points were collected. Sentences were also categorized based on their communicative functions: imperative, declarative, interrogative, and exclamatory. The dominant shifts found were structure shift (29.02%), intra-system shift (28.13%), and unit shift (24.55%). A single sentence may contain multiple translation shifts, with structure shift being the most frequently occurring type, followed by unit shift and intra-system shift, reflecting the translator's need to reorganize sentence structure, adjust grammatical units, and navigate system differences to achieve a natural and accurate target-language expression. Overall, the translation result for Honor of Kings' in-game event page sentences produces an acceptable value of 2.58.